Sodium-doped MgO/NbOPO4 toward highly selective ketonization of aldoses - Da-Ming, Gao; Wei, Guihua; Li, Changzhi; Fujino, Hidemi; Huang, Kai; Liu, Haichao; Yin, Xiaojing (New journal of chemistry, 2025)
The study aimed to investigate the catalytic effects of alkali metal-doped (Li+, Na+, and K+) magnesia supported by niobium phosphate on the ketonization of aldo-saccharides. The catalytic results showed that Na–MgO/NbP exhibits higher ketose selectivity than Li- and K–MgO/NbP. Compared to undoped MgO/NbP, doping Na+ ions at a molar ratio of 5–10% increased both the amount and density of basic sites. The EDS and ESR analyses showed that Na+ ions were uniformly distributed on the surface of the xNa–MgO/NbP catalyst, and the oxygen vacancies of xNa–MgO/NbP were increased with an increase in the amount of doped Na+ ions, which consequently accelerated the reaction rates. XPS analysis and UV-adsorption measurements indicated that Na+ doping had an electron-donating effect, diminishing the positive charge of Mg2+ ions. The ketose selectivity increased within the 10–20% Na+ doping range, while the yield of ketose remained relatively unchanged when treating aldoses with xNa–MgO/NbP catalysts. Na–MgO/NbP could give a ketose productivity of up to 44.8 g kg-solution−1 h−1 when treating 20.0 wt% glucose with a catalyst loading as low as 0.005 g g-solution−1, achieving a catalyst efficiency of 8.96 g g-catalyst−1 h−1. Further kinetic analysis revealed two types of catalytic sites on the surface: one catalyzed ketonization, while the other is primarily responsible for the decomposition of the saccharides.